Indonesian EFL Teachers' Perspectives of Self-Regulation in Reading - Kristian Florensio Wijaya (ELT Worldwide: Journal of English Language Teaching, 2022)
ABSTRACTIt has been a widespread belief that to be more successful readers, Indonesian EFL teachers are strongly suggested to inculcate a higher degree of self-regulation within their learners. Some researchers hold a strong belief that robust self-regulation construction will breed more proficient, well-organized, and autonomous L2 readers due to the presence of long-lasting reading learning endeavors. This present small-scale qualitative study was a further attempt to profoundly investigate Indonesian EFL teachers’ perspectives of self-regulation in reading. One major research problem was formulated in this study namely what are Indonesian EFL teachers’ specific perspectives toward the utilization of self-regulation in L2 reading activities? Responding to this proposed research problem, narrative inquiry manifested in 5 open-ended written narrative inquiry questions were addressed for 2 invited Indonesian EFL teachers graduating from English Education Master Study Program, Sanata Dharma University, Yogyakarta. The obtained research results highly prompted all EFL teachers to be more supportive reading learning facilitators by introducing their learners to self-regulation concepts to transfigure them to become more resilient, persistent, and competent target language readers. Keywords: self-regulation, EFL teachers’ perspectives, narrative inquiry